"A Crazy Roller Coaster at the End": A Qualitative Study of Death Preparedness With Caregivers of Persons With Dementia. (August 2020) - Durepos, Pamela; Ploeg, Jenny; Sussman, Tamara; Akhtar-Danesh, Noori; Kaasalainen, Sharon
Introduction: Caregivers of persons with dementia experience challenges that can make preparing for end-of-life particularly difficult. Feeling prepared for death is associated with caregiver well-being in bereavement and is promoted by strategies supporting a palliative approach. Further conceptualization of caregiver preparedness for death of persons with dementia is needed to guide the practice of healthcare providers and to inform development of a preparedness questionnaire. Objectives: We aimed to: 1) explore the end-of-life experiences of caregivers of persons with dementia to understand factors perceived as influencing preparedness; and 2) identify the core concepts (i.e., components), barriers and facilitators of preparedness for death. Methods: This study used an interpretive descriptive design. Semi-structured interviews were conducted with sixteen bereaved caregivers of persons with dementia, recruited from long-term care homes in Ontario. Data was analyzed through reflexive thematic analysis. Findings: Four themes were interpreted including: 'A crazy rollercoaster at the end' which described the journey of caregivers at end-of-life. The journey provided context for the development of core concepts (i.e., components) of preparedness represented by three themes: 'A sense of control, 'Doing right' and 'Coming to terms'. Conclusion: The study findings serve to expand the conceptualization of preparedness and can guide improvements to practice in long-term care. Core concepts, facilitators and influential factors of preparedness will provide the conceptual basis and content to develop the Caring Ahead: Preparing for End-of-Life with Dementia questionnaire.